THE TRANSLATION OF ENGLISH NOUN PHRASE INTO INDONESIAN - Herlina Lindaria Simanjuntak (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2020)
Many Indonesian’s students face the difficulties in translating English noun phrase into Indonesian. English and Indonesia have different structure. Meanwhile, one of the important elements in building a sentence is noun phrase. English noun phrases have some possibilities of translation result from the source language (SL) into the target lagnuage, Indonesian (TL). Hence, the researcher does the research which is entitled The Translation of English Noun Phrase Into Idonesian. The aims of this research are to find out the translations of English noun phrases into Indonesian. This research uses qualitative method. The source of data is “Sidney Sheldon's Memory of Midnight” and its translated version, “Padang Bayang Kelabu”, by Budijanto T. Pramono. The result of this research shows that there are four categories of translating English noun phrases into Indonesian, namely English noun phrases translated using the word yang, Plural English noun phrases translated into singular, English noun phrases translated using the word, and Elnglish noun phrases which are not translated literally. The conclusion of this research also shows that the change in the form and orders of the nouns phrases which is a noun as the head and also the sequence of modifiers, meanwhile without changing its meanings.